1.5) Differential equation is "y''' - 2y'' + 2y=0" and "\\phi(x)= e^{rx}" is solution of this differential equation, hence "\\phi(x)" holds the differential equation.
Now,
"y = \\phi(x) = e^{rx}, y' = r e^{rx}, y'' = r^2 e^{rx} + e^{rx}, \\\\ y''' = r^3e^{rx} + 2re^{rx} +re^{rx} = r^3e^{rx} + 3re^{rx}".
Hence by putting in differential equation, we ger
"e^{rx} (r^3+3r - 2r^2 -2 +2) = 0"
Since, "e^{rx} \\neq 0, \\implies r^3-2r^2 + 3r =0"
"\\implies r(r^2-2r+3) =0 \\implies r=0, r = \\frac{2\\pm \\sqrt{4-12}}{2} = 1\\pm\\sqrt{2} i" .
Two roots are imaginary, so real largest constant is 0.
1.6) Differential equation is "3x^2y''+11xy'-3y =0" .
"y = x^n" is solution when it holds the differential equation.
Now, "y = x^n, y' = nx^{n-1}, y'' = n(n-1) x^{n-2}"
By putting, we get
"\\implies (3n(n-1)+11n-3)x^n=0\n\\implies 3n^2 +8n-3=0 \\\\\nSo, \\ 3n^2+9n-n-3=0 \\implies (3n-1)(n+3)=0\n\\\\\n\\implies n = \\frac{1}{3}, -3."
Smallest n is -3.
Comments
Leave a comment